Oral hygiene practices and knowledge among stroke-care nurses: A multicentre cross-sectional study - Ab. Malik N.; Mohamad Yatim S.; Hussein N.; Mohamad H.; McGrath C. (Blackwell Publishing Ltd, 2024)
Indexed by Scopus